2002
DOI: 10.1093/clinchem/48.8.1212
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Filterable and Nonfilterable mRNA in the Plasma of Cancer Patients and Healthy Individuals

Abstract: Background: As RNA is labile, we investigated whether circulating RNA in human plasma may be present in a particle-associated form. Methods: Blood was collected from 27 healthy individuals and 16 hepatocellular carcinoma (HCC) patients. The plasma from each individual was processed by two means: filtration through filters with different pore sizes (from 5 μm to 0.22 μm) and ultracentrifugation. We assessed plasma RNA content by a real-time quantitative reverse transcription-PCR assay for glycera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(94 citation statements)
references
References 15 publications
7
85
0
2
Order By: Relevance
“…We found in our present study that concentrations of cell-free mitochondrial plasma DNA and mRNA in patients with cancer were generally higher than in healthy control subjects, consistent with previous reports. (14,15) We also found that changes in mitochondrial DNA concentrations showed a pattern Plasma DNA concentration showed decreasing ( ) or increasing ( ) tendency during RT period; unclassified, changing without any tendency; peak +, DNA concentration increasing with a transient peak followed by decreasing; day, day of transient peak; peak %, ratio of DNA concentration at transient peak to that before treatment; local, local recurrence; CR, complete remission; dis met, distant metastasis; resi, residual tumor; A/D, alive with disease; A, alive without disease; D, dead of disease; d, dead of other cause. doi: 10.1111/j.1349-7006.2008.01021.x © 2008 Japanese Cancer Association independent of 100-bp and 400-bp genomic DNA concentrations during radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We found in our present study that concentrations of cell-free mitochondrial plasma DNA and mRNA in patients with cancer were generally higher than in healthy control subjects, consistent with previous reports. (14,15) We also found that changes in mitochondrial DNA concentrations showed a pattern Plasma DNA concentration showed decreasing ( ) or increasing ( ) tendency during RT period; unclassified, changing without any tendency; peak +, DNA concentration increasing with a transient peak followed by decreasing; day, day of transient peak; peak %, ratio of DNA concentration at transient peak to that before treatment; local, local recurrence; CR, complete remission; dis met, distant metastasis; resi, residual tumor; A/D, alive with disease; A, alive without disease; D, dead of disease; d, dead of other cause. doi: 10.1111/j.1349-7006.2008.01021.x © 2008 Japanese Cancer Association independent of 100-bp and 400-bp genomic DNA concentrations during radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Specific primers and fluorescent probes for SARS-CoV and GAPDH mRNA detection (as described previously by us 13 ) were purchased from Applied Biosystems (table 2). The SARS-CoV primers and probe perfectly matched all available genomic sequences on GenBank.…”
Section: Q-rt-pcr Assaymentioning
confidence: 99%
“…Circulating RNA has been shown to be associated with subcellular particles of different sizes, which are removable by filtration and ultracentrifugation. 18 Approximately 70% of hPL and ␤-hCG mRNA can be removed from the maternal plasma by filtering the plasma sample through a 0.45-m filter. One possible source of these particle-associated placental RNA molecules would be the apoptotic shedding of microparticles from the placenta into the maternal circulation.…”
Section: Particalitymentioning
confidence: 99%